2020
DOI: 10.1039/c9bm01956a
|View full text |Cite
|
Sign up to set email alerts
|

A riboflavin–ultraviolet light A-crosslinked decellularized heart valve for improved biomechanical properties, stability, and biocompatibility

Abstract: Riboflavin–ultraviolet light A could effectively crosslink a decellularized heart valve to improve its biomechanical properties, stability and biocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…The mechanical properties of the DPAVL, DPAVL‐PL(NO x ), and DPAVL‐PL(O 3 ) were tested by the electronic mechanical testing machine (CMT 2102) after treatment. The mechanical test method is similar to that reported in Liu et al, [ 28 ] and the results are shown in Figure 2. Young's modulus is a physical quantity describing the deformation resistance of a solid material, which can be obtained by measuring the slope of the stress–strain curve in the high‐strain region.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The mechanical properties of the DPAVL, DPAVL‐PL(NO x ), and DPAVL‐PL(O 3 ) were tested by the electronic mechanical testing machine (CMT 2102) after treatment. The mechanical test method is similar to that reported in Liu et al, [ 28 ] and the results are shown in Figure 2. Young's modulus is a physical quantity describing the deformation resistance of a solid material, which can be obtained by measuring the slope of the stress–strain curve in the high‐strain region.…”
Section: Introductionsupporting
confidence: 56%
“…To check the surface morphology change of the DPAVL, scanning electron microscopy (SEM; JSM‐6510; Japan Electronics Co., Ltd.) was applied, and the experimental method is similar to that reported in Liu et al [ 28 ] The SEM images of the DPAVL‐PL(NO x ) and DPAVL are shown in Figures 6a,i and 6a,ii, respectively. The results show that there is no significant difference in the microstructure between the DPAVL‐PL(NO x ) and DPAVL.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in 2019, the tissue engineering market reached USD 25.4 billion, and over the span of 2017–2022, the market is on the track to increase 17.22% in CAGR [ 84 ]. Complementarily, the biomaterials market is particularly successful with a growing demand for products such as medical implants to be utilized as the primary scaffold of tissue-engineered heart valves [ 85 ], as well as nano-, micro-, and macroscale drug systems developed for cancer immunotherapy and antitumor T-cell immunity [ 86 ]. To add in, the biomaterials sector is poised to increase from a worth of USD 105 billion in 2019 to USD 207 billion in 2024, which reaches a 14.4% CAGR [ 87 ].…”
Section: Challenges and Perspectives For Ha-enzyme Applications: A Complementary Market Analysismentioning
confidence: 99%
“…Liu et al developed a photo‐crosslinking reaction using riboflavin and ultraviolet light to improve the biomechanical properties and stability of decellularized heart valve (DHV), a common scaffold for tissue‐engineered heart valves. HUVECs exhibited excellent adhesion to the riboflavin‐ultraviolet cross‐linked DHV and the scaffold displayed slow degradation, non‐calcification, and lower pro‐inflammatory response in a rat in vivo model 104 …”
Section: Progress In Cardiovascular Bioprintingmentioning
confidence: 99%
“…In the sphere of bioengineering, the fabrication of vasculature holds tremendous significance because it represents one of the major limiting factors to produce any living tissue construct 30,103‐105 . This is because a functional vascular network is vital for any construct larger than 200 micrometers in diameter in order to supply nutrients and retain metabolic activity to ensure tissue health 104 . It would not be an exaggeration to say that the progress of the entire field of bioengineering is directly dependent on the progress made in vascular network fabrication.…”
Section: Progress In Cardiovascular Bioprintingmentioning
confidence: 99%